Preparation of adsorbent based on cotton fabric and ZIF-8 and application of adsorbent in antibiotic adsorption
By growing ZIF-8 adsorbents in situ to form columnar structures on cotton fabrics, the problem of tetracycline pollution is solved, and antibiotics in the water environment is efficiently removed, demonstrating its application potential in environmental restoration.
Patent Information
- Application Number
- CN202411512757.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-03
AI Technical Summary
Tetracycline, as a broad-spectrum antibiotic, is not completely absorbed after use, causing it to flow into nature, causing environmental pollution and posing a threat to human health. The thermal stability and chemical stability of existing adsorbent materials are insufficient, making it difficult to effectively remove antibiotic pollution in the environment.
Using adsorbents based on cotton fabrics and ZIF-8, ZIF-8 is fixed on cotton fabrics by in-situ growth, and the adsorbents forming columnar structures are grown multiple times, utilizing its high specific surface area and excellent tetracycline adsorption properties. Achieve effective adsorption of antibiotics in the aqueous environment.
The prepared ZIF-8@ cotton fabric adsorbent has good hydrophilicity and tetracycline adsorption properties, and can efficiently remove tetracycline under different pH conditions, significantly improving the treatment effect of antibiotic pollution in the water environment.
Smart Images

Figure CN119236898A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanocomposite, and specifically relates to the preparation of an adsorbent based on cotton fabric and ZIF-8 and the application of the adsorbent in antibiotic adsorption. Background Art
[0002] Tetracycline is one of the most commonly used broad-spectrum antibiotics and is widely used in the treatment of human bacterial infections and as a growth promoter in aquaculture and other animal husbandry. These used but not fully absorbed tetracyclines will continue to flow into nature and remain undegraded in soil and water sources for many years, causing environmental pollution and posing a threat to human health. Therefore, there is an urgent need to develop effective and economical environmental remediation technologies.
[0003] ZIF-8 is a type of tetracycline adsorption material that has been widely studied in recent years. As a branch of MOFs materials, it not only overcomes the problems of poor thermal stability and poor chemical stability of some MOFs materials, but also has the advantages of high specific surface area, ordered pore structure, high crystallinity, multi-metal sites, good polymer compatibility, and structural diversity of MOFs materials. ZIF-8 is a zinc-based imidazole molecular sieve framework prepared from divalent zinc ions and dimethylimidazole as raw materials, and has a microporous structure. At the same time, it also has the characteristics of easy synthesis, low cost, good water stability and chemical stability. The adjustable nature of ZIF-8 structure also helps it to be applied in different environments. It can be tailored to specific application sites by adjusting its topological structure, pore size and chemical composition to design different structures. Summary of the invention
[0004] The present invention aims to address the current environmental pollution problem and proposes an innovative and feasible tetracycline adsorbent based on cotton fabric and ZIF-8 with a columnar structure and strong hydrophilicity to achieve the adsorption of antibiotics in water environments and meet the growing application needs of water pollution treatment.
[0005] The preparation method of the adsorbent based on cotton fabric and ZIF-8 of the present invention comprises the following steps: Step 1: ZIF-8 is combined with cotton fabric by in-situ growth. Zinc nitrate hexahydrate, dimethylimidazole and cysteine are used as raw materials and deionized water is used as solvent to prepare zinc nitrate aqueous solution, dimethylimidazole aqueous solution and dimethylimidazole and cysteine two-component aqueous solution respectively; Step 2: Wash the cotton fabric with ethanol and deionized water and dry it; Step 3: soaking the dried cotton fabric obtained in step 2 in the zinc nitrate aqueous solution prepared in step 1, so that the divalent zinc ions are combined with the hydroxyl groups on the glucose units of the cotton fabric on the surface of the cotton fabric fiber through coordination; after the soaking, the cotton fabric is taken out and washed with ethanol and deionized water to remove the loose and unconnected divalent zinc ions; Step 4: The cotton fabric with divalent zinc ion coordination obtained in step 3 is placed in a dimethylimidazole aqueous solution for soaking and reaction; after the reaction is completed, the cotton fabric is taken out, washed with ethanol and deionized water to remove unreacted substances, and dried to obtain a single-growth ZIF-8@cotton fabric-1 adsorbent material; Step 5: Repeat step 3 with the ZIF-8@cotton fabric-1 obtained in step 4, and then immerse the obtained cotton fabric in a two-component aqueous solution of dimethylimidazole and cysteine for reaction; after the reaction is completed, the cotton fabric is dried to prepare the secondary grown ZIF-8@cotton fabric-2 adsorbent material.
[0006] further: In the solution obtained in step 1, the concentration of the zinc nitrate aqueous solution is fixed at 0.2 mol / L, the concentration of the dimethylimidazole aqueous solution is fixed at 0.3 mol / L, the concentration of the dimethylimidazole in the two-component aqueous solution of dimethylimidazole and cysteine is 0.3 mol / L, and the concentration of cysteine is 0.01-0.05 mol / L.
[0007] In step 2, the cotton fabric is pretreated to remove impurities on the surface of the cotton fabric, which is helpful for exposing the hydroxyl groups of glucose units in the cotton fabric. The pretreated cotton fabric is dried at 40° C. to a constant weight.
[0008] In step 3, when the cotton fabric is immersed in the zinc nitrate aqueous solution for reaction, the immersion temperature is set to 50-70° C. and the immersion time is set to 3-4 hours to achieve the coordination effect between the divalent zinc ions and the hydroxyl groups on the glucose units of the cotton fabric.
[0009] In step 4, when the cotton fabric is immersed in the dimethylimidazole aqueous solution for reaction, the immersion temperature is set to 50-70°C and the immersion time is 3-4 hours. The in-situ growth of ZIF-8 on the cotton fabric is completed by the reaction of divalent zinc ions with dimethylimidazole. Then the cotton fabric is placed in an oven at 40°C until the cotton fabric is completely dried to obtain a single-growth ZIF-8@cotton fabric-1 adsorbent material.
[0010] In step 5, after repeating step 3 once, the cotton fabric is immersed in the two-component solution of dimethylimidazole / cysteine prepared in step 1 for reaction, and the immersion temperature is set to 50-70°C and the immersion time is 3-4h to obtain a secondary grown ZIF-8@cotton fabric-2 adsorbent material. The ZIF-8 crystals on the surface of the composite material present a columnar structure, and the composite material has excellent tetracycline adsorption performance.
[0011] The invention discloses an application of an adsorbent based on cotton fabric and ZIF-8 in adsorption of antibiotics.
[0012] Furthermore, the antibiotic is tetracycline.
[0013] Furthermore, the pH value of the system is 5-7, preferably 6.
[0014] The present invention has the following beneficial effects: 1. The ZIF-8@cotton fabric adsorbent material prepared by the present invention has a columnar structure.
[0015] 2. The ZIF-8@cotton fabric adsorbent material prepared by the present invention has good hydrophilicity, environmental friendliness and tetracycline adsorption performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The figures are scanning electron microscope photos of the cotton fabric of single-growth ZIF-8 (a) and the cotton fabric of secondary-growth ZIF-8 (b) prepared in Example 1 of the present invention. As can be seen from the figure, the cotton fabric of single-growth ZIF-8 presents the tetrahedral morphology of traditional ZIF-8, while the crystal morphology of the cotton fabric of secondary-growth ZIF-8 changes from the original regular tetrahedron to a columnar structure with a larger specific surface area, which helps to improve the adsorption performance of antibiotics.
[0017] Figure 2 This is the infrared spectrum of the columnar ZIF-8 cotton fabric composite adsorbent material prepared in Example 1 of the present invention. From the figure, it can be seen that ZIF-8 is successfully grown on the cotton fabric.
[0018] Figure 3 The results show the adsorption of tetracycline hydrochloride by the columnar ZIF-8 cotton fabric adsorbent prepared in Example 1 under different pH conditions. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative ideas belong to the scope of protection of the present invention. Embodiment 1:
[0020] The preparation method of the tetracycline adsorbent based on cotton fabric and ZIF-8 in this embodiment comprises the following specific steps: Step 1: Dissolve 0.02 mol zinc nitrate hexahydrate, 0.03 mol dimethylimidazole and 0.03 mol dimethylimidazole / 0.005 mol cysteine in 100 mL of deionized water to obtain zinc nitrate aqueous solution (0.2 mol / L), dimethylimidazole aqueous solution (0.3 mol / L), and dimethylimidazole aqueous solution and cysteine two-component solution (0.3 mol / L+0.05 mol / L), respectively.
[0021] Step 2: pretreating the cotton fabric with ethanol and deionized water to remove impurities on the surface of the cotton fabric, which is helpful for exposing the hydroxyl groups of the glucose units of the cotton fabric. The pretreated cotton fabric is dried at 40° C. to constant weight.
[0022] Step 3: Place the cotton fabric in a beaker containing an aqueous solution of zinc nitrate, seal the beaker and place it in a 60°C oven for 3.5 h to achieve the coordination of the divalent zinc ions with the hydroxyl groups on the glucose units of the cotton fabric. After soaking, take out the cotton fabric and wash it with ethanol and deionized water to remove loose and unconnected divalent zinc ions.
[0023] Step 4: Place the cotton fabric prepared in step 3 into a beaker containing a dimethylimidazole aqueous solution, and seal the beaker and place it in a 60°C oven for 3.5 h to complete the in situ growth of ZIF-8 on the cotton fabric through the reaction of divalent zinc ions and dimethylimidazole; then take out the cotton fabric and place it in a 40°C oven until the cotton fabric is completely dried to obtain a single-growth ZIF-8@cotton fabric-1 adsorbent material.
[0024] Step 5: Repeat step 3 once for the cotton fabric prepared in step 4, and then put the obtained cotton fabric into the dimethylimidazole / cysteine two-component solution prepared in step 1 to obtain the secondary grown ZIF-8@cotton fabric-2 adsorbent material. Embodiment 2:
[0025] Step 1: First, 0.02 mol zinc nitrate hexahydrate and 0.03 mol dimethylimidazole were dissolved in 100 mL of deionized water to obtain a zinc nitrate aqueous solution (0.2 mol / L) and a dimethylimidazole aqueous solution (0.3 mol / L), respectively.
[0026] Step 2: pretreating the cotton fabric with ethanol and deionized water to remove impurities on the surface of the cotton fabric, which is helpful for exposing the hydroxyl groups of the glucose units of the cotton fabric. The pretreated cotton fabric is dried at 40°C.
[0027] Step 3: Place the cotton fabric in a beaker containing an aqueous solution of zinc nitrate, seal the beaker and place it in a 60°C oven for 3.5 h to achieve the coordination of the divalent zinc ions with the hydroxyl groups on the glucose units of the cotton fabric. After soaking, take out the cotton fabric and wash it with ethanol and deionized water to remove loose and unconnected divalent zinc ions.
[0028] In step 4, the cotton fabric prepared in step 3 is placed in a beaker containing a dimethylimidazole aqueous solution, and the beaker is sealed and placed in a 60°C oven for 3.5 h to complete the in situ growth of ZIF-8 on the cotton fabric through the reaction of divalent zinc ions and dimethylimidazole; then the cotton fabric is placed in a 40°C oven until the cotton fabric is completely dried to obtain a single-growth ZIF-8@cotton fabric-1 adsorbent material. Embodiment 3:
[0029] The concentration of the two-component solution of dimethylimidazole and cysteine prepared in step 1 of Example 1 was adjusted to (0.3 mol / L+0.01 mol / L), and the other components and operations remained unchanged. At this time, the ZIF-8 crystal morphology did not change significantly compared with the single growth, and basically still presented a regular tetrahedron, but compared with the single growth, it can be seen that the ZIF-8 on the cotton fabric surface is more dense. Embodiment 4:
[0030] The concentration of the two-component solution of dimethylimidazole and cysteine prepared in step 1 of Example 1 was adjusted to (0.3 mol / L+0.02 mol / L), and the other components and operations remained unchanged. ZIF-8 almost completely covered the surface of each fiber of the cotton fabric, but at this time ZIF-8 still showed a common regular tetrahedral structure. Embodiment 5:
[0031] The concentration of the two-component solution of dimethylimidazole and cysteine prepared in step 1 of Example 1 was adjusted to (0.3 mol / L + 0.03 mol / L), and the other components and operations remained unchanged. As the concentration of cysteine increased, it can be observed that the surface of the cotton fabric fiber was completely covered by ZIF-8. Compared with the sparse distribution of single growth, the ZIF-8 on the surface of the cotton fabric at this time appeared partially stacked, and a small amount of columnar structure appeared. Embodiment 6:
[0032] The concentration of the two-component solution of dimethylimidazole and cysteine prepared in step 1 of Example 1 was adjusted to (0.3 mol / L + 0.04 mol / L), and the other components and operations remained unchanged. At this time, it can be observed that the crystal structure of ZIF-8 covering the surface of the cotton fabric fiber has changed significantly, and the stacked ZIF-8 gradually presents a clear columnar structure. Example 7: ZIF-8 cotton fabric adsorption experiment with different secondary growth times
[0033] 10 mg of all the ZIF-8 cotton fabric adsorbents obtained in Examples 1-6 were taken respectively, and these adsorbents were respectively put into 100 mL of simulated wastewater with a concentration of 50 mg / L tetracycline hydrochloride (pH 6), and the adsorption reaction was carried out for 24 hours at a temperature of 25°C and a shaking rate of 150 Hz. After filtering with a 0.45 μm filter membrane, the concentration of the remaining tetracycline hydrochloride in the solution was determined by an ultraviolet spectrophotometer, and the adsorption efficiency results are shown in the following table: Example 8: Adsorption experiments under different pH conditions
[0034] 50 mL of simulated wastewater with a concentration of 100 mg / L tetracycline hydrochloride was prepared, and 10 mg of the columnar ZIF-8 cotton fabric adsorbent prepared by the method of Example 1 was added to each group of simulated wastewater. After the adsorption reaction was carried out for 24 hours at pH values of 4, 5, 6, 7, and 8, the temperature was 25°C, and the shaking rate of the shaker was 150 Hz, the solution was filtered with a 0.45 μm filter membrane, and then the residual tetracycline hydrochloride concentration in the solution was measured by an ultraviolet spectrophotometer to examine its adsorption capacity.
[0035] The above experimental test results are as follows Figure 3 As shown, Figure 3 The results show the test results of the adsorption of tetracycline hydrochloride by the columnar ZIF-8 cotton fabric adsorbent prepared in Example 1 under different pH conditions. The optimal pH value is 6. When pH = 6, the maximum adsorption of tetracycline hydrochloride is 478.15 mg / g. It can be seen that the columnar ZIF-8 cotton fabric adsorbent prepared in Example 1 has a good removal ability for tetracycline hydrochloride under the condition of pH = 6.
[0036] In summary, the present invention provides a novel preparation method of a columnar ZIF-8 crystal morphology adsorbent material, wherein ZIF-8 is fixed on cotton fabric by in-situ growth, and then multiple growths of ZIF-8 crystals are achieved by repeated experiments, thereby obtaining ZIF-8 with a columnar structure. The morphology and size of the ZIF-8 crystals are controlled by changing the time of the secondary growth, so that the adsorbent material has a larger specific surface area and enhances the adsorption performance of the composite material.
[0037] Note: The above examples are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above examples, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present invention should be covered by the scope of the claims of the present invention.
Claims
1. A method for preparing an adsorbent based on cotton fabric and ZIF-8, characterized in that The steps include: Step 1: using zinc nitrate hexahydrate, dimethylimidazole and cysteine as raw materials and deionized water as solvent, respectively preparing a zinc nitrate aqueous solution, a dimethylimidazole aqueous solution, and a two-component aqueous solution of dimethylimidazole and cysteine; Step 2: Wash the cotton fabric with ethanol and deionized water and dry it; Step 3: soaking the dried cotton fabric obtained in step 2 in the zinc nitrate aqueous solution prepared in step 1, so that the divalent zinc ions are combined with the hydroxyl groups on the glucose units of the cotton fabric on the surface of the cotton fabric fiber through coordination; after the soaking, the cotton fabric is taken out and washed with ethanol and deionized water to remove the loose and unconnected divalent zinc ions; Step 4: The cotton fabric with divalent zinc ion coordination obtained in step 3 is placed in a dimethylimidazole aqueous solution for soaking and reaction; after the reaction is completed, the cotton fabric is taken out, washed with ethanol and deionized water to remove unreacted substances, and dried to obtain a single-growth ZIF-8@cotton fabric-1 adsorbent material; Step 5: Repeat step 3 with the ZIF-8@cotton fabric-1 obtained in step 4, and then immerse the obtained cotton fabric in a two-component aqueous solution of dimethylimidazole and cysteine for reaction; after the reaction is completed, the cotton fabric is dried to prepare the secondary grown ZIF-8@cotton fabric-2 adsorbent material.
2. The preparation method according to claim 1, characterized in that: In the solution obtained in step 1, the concentration of the zinc nitrate aqueous solution is 0.2 mol / L, the concentration of the dimethylimidazole aqueous solution is 0.3 mol / L, and the concentration of the dimethylimidazole in the two-component aqueous solution of dimethylimidazole and cysteine is 0.3 mol / L, and the concentration of cysteine is 0.01-0.05 mol / L.
3. The preparation method according to claim 1, characterized in that: In step 3, when the cotton fabric is immersed in the zinc nitrate aqueous solution for reaction, the immersion temperature is set to 50-70° C. and the immersion time is set to 3-4 hours to achieve the coordination effect between the divalent zinc ions and the hydroxyl groups on the glucose units of the cotton fabric.
4. The preparation method according to claim 1, characterized in that: In step 4, when the cotton fabric is immersed in the dimethylimidazole aqueous solution for reaction, the immersion temperature is set to 50-70° C. and the immersion time is set to 3-4 hours.
5. The preparation method according to claim 1, characterized in that: In step 5, after repeating step 3 once, the cotton fabric is immersed in the two-component solution of dimethylimidazole and cysteine prepared in step 1 for reaction, the immersion temperature is set to 50-70°C, and the immersion time is set to 3-4h to obtain the secondary grown ZIF-8@cotton fabric-2 adsorbent material.
6. Use of the adsorbent based on cotton fabric and ZIF-8 prepared according to any one of the preparation methods of claims 1 to 5 in the adsorption of antibiotics.
7. The use according to claim 6, characterized in that: The antibiotic is tetracycline.
8. The use according to claim 6, characterized in that: The pH value of the adsorption system is 5-7.
